An Efficient Simulated Annealing Algorithm for Economic Load Dispatch Problems - Hardiansyah Hardiansyah; Junaidi Junaidi; Yohannes MS Yohannes MS (Universitas Ahmad Dahlan, 2013)
This paper presents an efficient simulated annealing (SA) algorithm with a single decision variable to solve the economic load dispatch (ELD) problems. The philosophy involves the introduction of a new decision variable through a prudent mathematical transformation of the relation between the decision variable and the optimal generations. The objectives of ELD problems in electric power generation is to programmed the devoted generating unit outputs so as to meet the mandatory load demand at lowest amount operating cost while satisfying all units and system equality and inequality constraints. Global optimization approaches is inspired by annealing process of thermodynamics. The proposed SA algorithm presented here is applied to two case studies, which analyze power systems having three, and six generating units. The results determined by the proposed approach are compared to those found by conventional quadratic programming (QP) and genetic algorithm (GA).